ASSORTMENTS OF DRUGS AND TECHNOLOGICAL RECEIVES, WHICH THE FIRST DOCTORS APPLIED - K. S. Guzev (Разработка и регистрация лекарственных средств, 2019)
The paper presents information on how the Sumerians, doctors of Egypt, Ancient Greece and the Roman Empire treated their patients two thousand years or more ago. An attempt is made to analyze the assortments of medicines and technological methods used by physicians of different states and cultures. It is established that they had many similarities and consisted of representatives of the vegetable and animal kingdoms, as well as the world of minerals. The technology of preparation of medicines consisted of simple operations, which, however, improved over time. Most of the medicines used by ancient doctors have lost their meaning, although some of them are still valid today.